A comprehensive review of Quercus semecarpifolia Sm.: An ecologically and commercially important Himalayan tree - Rawat, Balwant; Rawat, Janhvi M.; Purohit, Sumit; Singh, Gajendra; Sharma, Pradeep Kumar; Chandra, Anup; Shabaaz Begum, J. P.; Venugopal, Divya; Jaremko, Mariusz; Qureshi, Kamal A. (Frontiers in Ecology and Evolution, 2022)
Himalayan mountains forests have been a potential candidate for the investigation of perturbations due to the complex geography in which they sustain and the sensitivity of the species towards human disturbance and climate change. Among various tree species, brown oak (Quercus semecarpifolia) a very important component of the Himalayan mountains has been identified as a keystone species due to its substantial economical and ecological benefits. Maintenance of microclimate and suitable habitats with a rich source of natural resources make Quercus semecarpifolia the most preferred forest for luxuriant growth of ground flora, shelter for fauna and multipurpose uses by local people. In a climax community, it is playing a critical role in environmental balance at both the local and the regional levels. Unfortunately, it has become one of the most over-exploited tree species of the Himalayan region over the last few decades due to its high demand for dry season fodder and firewood. The wide range of seedling distribution 348 to 4663 individuals ha-1 is evidence of disturbance accompanied by poor regeneration in Quercus semecarpifolia forests. Moreover, litter accumulation and grass cover adversely affect seed germination. The ecological cost of oak forest degradation is perhaps more important and damage is irreversible. Thus continuous demand and extensive threats accompanied by poor regeneration have drawn the attention of stakeholders to conserve this species. However, propagation protocol especially the pre-sowing treatment of the species has not been impressive for large-scale multiplication. The present review is comprehensive information on distribution, phenology, regeneration pattern, human threat, conservation approaches and management of Quercus semecarpifolia in the Himalayan region.